Collaborative Projects and Memoranda of Agreement (MOA)- Fact Sheet - Dru McGill; Davina Two Bears; Julie Woods; Research Ethics and Intellectual Property Working Group (Simon Fraser University, 2015)
The IPinCH Fact Sheet initiative aims to provide information and guidance on important issues emerging in cultural heritage research. RESOURCESDeclarationsReportsPublicationsPresentationsVideosPodcastsFact SheetsTeaching ResourcesReading ListsLinks